2020
DOI: 10.1016/j.celrep.2020.01.098
|View full text |Cite
|
Sign up to set email alerts
|

Entropic Bristles Tune the Seeding Efficiency of Prion-Nucleating Fragments

Abstract: Graphical Abstract Highlights d A short peptide derived from Sup35 (p103-113) forms rigid amyloid fibrils d p103-113 fibrils can induce infectious Sup35 NM prions in mammalian cells d Embedding p103-113 in an N-rich sequence increases fibril brittleness d Increased fibril brittleness enhances prion-inducing capacity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 69 publications
(83 reference statements)
0
16
0
Order By: Relevance
“…This does not exclude modulating effects of other regions, even by regions that are not incorporated in the fibre core, such as the fuzzy coat observed in many amyloids 29 . However, by and large in disease amyloids assembly kinetics and stability are both would be sufficient to drive that process [35][36][37] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This does not exclude modulating effects of other regions, even by regions that are not incorporated in the fibre core, such as the fuzzy coat observed in many amyloids 29 . However, by and large in disease amyloids assembly kinetics and stability are both would be sufficient to drive that process [35][36][37] .…”
Section: Discussionmentioning
confidence: 99%
“…gatekeeper mutations at the flanks of APRs) together with mutations favouring more rapid alternative modes of assemblies (e.g. out of register β-sheet assembly) would be sufficient to drive that process 35-37 .…”
Section: Discussionmentioning
confidence: 99%
“…The role of amino acid composition has also been indirectly expanded to regions flanking APRs in protein sequences. Our recent work has shown that single residues flanking APRs in protein sequences can act as gatekeepers that attenuate aggregation propensity [138,[163][164][165][166], whereas sequence stretches of high disorder can affect the transmissibility of functional prion APRs by modulating aggregation morphology [167].…”
Section: Is Sequence Specificity a Determining Factor In Amyloid Hetementioning
confidence: 99%
“…Only when Doc binds and folds these IDP tails can operator binding proceed with high affinity and the phd/doc operon be repressed. This mechanism is further related to the action of entropic bristles, which are IDP tails that can act as solubilizers to prevent aggregation (Santner et al, 2012), tune prion nucleation (Michiels et al, 2020) and tune the energy landscape of proteins in general with respect to protein assemblies and ligand binding and association (Keul et al, 2018;Niemeyer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%